From Control to Mediation - Fukuta, Takanari (COMMONS, 2022)
In this essay, the author examines the function of language in caregiving based on his recollections of his father's caregiving experiences, from a media researcher’s viewpoint.　In the process of caring, a considerable amount of records were left, including detailed notes on father's condition, as well as notes to share information among the staff. From these records, we can see that language mainly served a "control" function, especially in the early stages of caregiving. Those were intended to control father's life as well as control care staff. Therein lies the author's unconscious desire for domination.　However, such a desire was later transformed. The words in the notebook came to exhibit "mediating" features, instead of control. In addition, the whole process of care had turned into a sort of "media experience". The author examined this shift from "control" to "mediation," referring to Asa Ito and Roland Barthes.　At the end, the author pointed out the characteristics of language in caregiving that cannot be recovered in the "control to mediation" scheme. Referring to psychiatrist Hisao Nakai's concept of "signs," the author discussed that the detailed notes were not only traces of his desire for control, but also an accumulation of "signs" perceived from his father's weakened life. Based on this understanding, language in caregiving can be considered to have functioned as a "medium" that connected the coming death with the present and the past. In other words, caregiving for the author had been a "media experience" in a double sense.